2009
DOI: 10.1007/s00192-009-0991-x
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation rate for traditional anterior vaginal repair: analysis of 207 cases with a median 4-year follow-up

Abstract: While the anatomical recurrence rates for cystocele following traditional anterior colporrhaphy might be high, the low reoperation rate at more than 4 years (3.4%) suggests that patient's symptoms might not be bothersome enough to require further surgery. Both subjective and anatomical outcomes are required to assess the outcome of both traditional and new prolapse procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…The learning curve and surgical skills are discussed to be related to mesh-erosion rates as well as mesh quality [22][23][24] and operation technique. These factors may contribute to the wide-ranging number of occurrence of mesh exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The learning curve and surgical skills are discussed to be related to mesh-erosion rates as well as mesh quality [22][23][24] and operation technique. These factors may contribute to the wide-ranging number of occurrence of mesh exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, pessaries have been used as a temporary measure to control symptoms while awaiting surgery, or as a permanent alternative to surgery for women who are medically unfit and those who have declined surgery or who wish to have children [9,10]. However, it has been shown that vaginal pessaries are a viable treatment option for any woman with POP [11][12][13]. Kapoor et al [13] reported that nearly two-thirds of women with symptomatic POP chose a vaginal pessary rather than surgery as the initial treatment.…”
Section: Introductionmentioning
confidence: 98%
“…The discrepancy between recurrence and reoperation rates has been previously reported. In a study of 207 cases that had anterior colporrhaphy, Kapoor et al reported a 12% recurrence rate with only a 3.4% reoperation rate (19). This discrepancy could be explained in different aspects.…”
Section: Discussionmentioning
confidence: 99%